KONSEP SYUKUR DALAM AL-QUR’AN DAN IMPLIKASINYA TERHADAP PENDIDIKAN ISLAM - Khulailiyah, Ahsanatul (ILJ: Islamic Learning Journal, 2023)
Knowing the concept of gratitude for Islamic education is very important, that building the concept of gratitude for Islamic education is an effort to foster a mentality that excels in both the knowledge and routine aspects of Islamic Education and also gives a positive response to Islamic education, about how the concept of gratitude is needed to build and improve Islamic education that is noble, disciplined and has achievement motivation. This research focuses on the concept of gratitude in Surat al-Baqarah verse 172 and its implications for Islamic education. This research includeslibrary research by collecting data from literature. In analyzing the data using the methoddescriptive analysis. By using an interpretative and normative approach. The results of the study state that the implications of the concept of gratitude for Islamic education in the study of Surat al-Baqarah verse 172 include: 1. Humans are obliged to always be grateful at all times, especially when they get pleasure. 2. Gratitude in Islamic education is the most important thing that will create a sense of qana'ah, patience, and sincerity. So that it can build Islamic education to be more disciplined, achievement and noble. The research results stated; 1). In essence, a person always gets favors, so because of that someone must be grateful at all times. 2). The implications of gratitude for Islamic education include: implications for educators, implications for students, implications for institutions. The author hopes that this research will continue to be developed so that lessons can be learned in everyday life.